2012
DOI: 10.1177/1533317512459798
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Neuroimaging Markers in Early Versus Late-Onset Alzheimer’s Disease

Abstract: Background Early-onset Alzheimer’s disease (EOAD) has been overshadowed by the more common late-onset AD (LOAD). Yet, the literature indicates EOAD may have less hippocampal-memory presentations and more focal neocortical localization early in the disease. Objective To evaluate these proposed differences between these two forms of AD and to explore what they inform about differences in AD-pathophysiology. Methods 21 EOAD and 24 LOAD patients matched for disease progression and severity were compared on neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 45 publications
2
40
1
1
Order By: Relevance
“…However, this differential pattern of memory impairment between EOAD and LOAD should be corroborated with further studies directed to specifically assess these patterns of memory impairment. In contrast to our findings, some previous studies reported lower scores in recognition memory tests in LOAD [12]. This result could be even anatomically explained with correlations of localization of hypometabolism observed in PET studies and regional cerebral atrophy with more involvement of hippocampal structures in patients with LOAD [10,14].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, this differential pattern of memory impairment between EOAD and LOAD should be corroborated with further studies directed to specifically assess these patterns of memory impairment. In contrast to our findings, some previous studies reported lower scores in recognition memory tests in LOAD [12]. This result could be even anatomically explained with correlations of localization of hypometabolism observed in PET studies and regional cerebral atrophy with more involvement of hippocampal structures in patients with LOAD [10,14].…”
Section: Discussioncontrasting
confidence: 85%
“…That is, differences between EOAD and LOAD have been reported in the rate of disease progression (faster in EOAD patients) [5][6][7], topographic distribution of cerebral atrophy in magnetic resonance imaging (MRI) studies (LOAD patients seem to be remarkably atrophic in the hippocampus, whereas EOAD in neocortical areas, such as the parietal, precuneus and posterior cingulate cortices) [8][9][10][11], location of metabolic deficits in positron emission tomography (PET) scans (EOAD in parietal regions and LOAD in inferior frontotemporal lobes including hippocampal region) [12][13][14] and prevalence of the presence of at least one ApoE e4 allele [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several FDG PET studies on presymptomatic FAD subjects showed the presence of regional parieto-temporal, posterior cingulate cortex (PCC) and medial temporal lobe hypometabolism on a background of wide-spread global CMRglc impairment (Fig. 1) [11,54,55].…”
Section: Fdg Pet and Presymptomatic Early-onset Fadmentioning
confidence: 99%
“…This is in agreement with previous studies that reported EOAD patients to have more prominent frontoparietal dysfunction than medial temporal dysfunction. 3,14,15 Our study also identified that LOAD patients have more positive symptoms of BPSD including delusions and irritability. Table 5 summarises the differences in BPSD between FAD and LOAD patients in our study and in other reported studies between EOAD and LOAD patients.…”
Section: Discussionmentioning
confidence: 58%